Rhyolites in the Emeishan large igneous province (SW China) with implications for plume-related felsic magmatism. (15th September 2018) - Hei, Hui-Xin; Su, Shang-Guo; Wang, Yu; Mo, Xuan-Xue; Luo, Zhao-Hua; Liu, Wen-Gang
Graphical abstract: Highlights: Two types of rhyolites are identified in the ELIP. Nb-Ta-poor rhyolites were formed through partial melting of the Yangtze basement. Nb-Ta-rich rhyolites have an age of 261.0 ± 1.7 Ma, coeval with the Emeishan magmatism. Nb-Ta-rich rhyolites are the products of assimilation-fractional crystallization. Abstract: In the Emeishan Large Igneous Province (ELIP), western Yangtze Block, SW China, minor amounts of silicic volcanic rocks (∼5%) are spatially and temporally associated with flood basalts. The distribution and origin of these silicic rocks are keys to understanding the processes associated with mantle plume activities. In the Binchuan and Panzhihua areas, southwestern ELIP, there are Nb-Ta-poor and Nb-Ta-rich rhyolites. Nb-Ta-poor rhyolites interlayered with basalts in the Binchuan area occur in the lower part of the Emeishan volcanic sequence and have a crustal origin. They are characterized by negative Nb-Ta anomalies, low εNd (t) and high 87 Sr/ 86 Sr(i) values, and zircon saturation temperatures (836–852 °C). Nb-Ta-rich rhyolites are associated with the main phase of the Emeishan volcanic sequence in the Binchuan and Panzhihua areas and are characterized by positive Nb-Ta anomalies, oceanic island basalt (OIB)-like trace element ratios, low 87 Sr/ 86 Sr(i) ratios, positive εNd (t) and εHf (t) values, and high A/CNK ratios and Fe∗s. In addition, they have high Ga/Al ratios, high field strength elements (HFSEs), and high zircon saturation temperatures (>920 °C), typical of aluminous A-type silicic rocks, similar to the spatially distributed syenitic intrusions of the ELIP. These Nb-Ta-rich rhyolites are best interpreted as hybrid products of crystal fractionation of high-Ti basaltic magmas, coupled with minor crustal assimilation (6–14%), on the basis of Rhyolite-MELTS and EC-AFC simulations. The temporal and spatial distributions of these two types of rhyolite reflect various extents of thermal and mass exchange between mantle-derived basaltic magma and crustal material above a mantle plume. When the plume head reached the base of the western Yangtze Block, enriched components in the lithospheric mantle were melted and the melts partially ponded near the crust-mantle boundary or in the lower crust where they induced partial melting of crustal materials to form Nb-Ta-poor rhyolites. During the main phase of volcanism, large magma chambers and extensive plumbing systems developed due to decompressional melting of the mantle plume. In this stage, abundant mafic-ultramafic and felsic intrusions were formed, and Nb-Ta-rich rhyolites and A-type granites were emplaced.